Heat lightning - Sandford, John 1944 February 23- (New York Berkeley, 2009)
Summoned by Lucas Davenport to investigate a pair of murders in which the victims are found with lemons in their mouths, Minnesota Bureau of Criminal Apprehension investigator Virgil Flowers struggles to find a connection that could prevent additional killings.
Keywords: Vietnam War, 1961-1975 -- Veterans -- Crimes against -- Fiction; Government investigators -- Minnesota -- Fiction; Minnesota -- Fiction; Mystery fiction